Impact of Use of Prezi-based Media on Learning Outcomes Indonesian Language Class Student XI at Muhammadiyah Rappang Vocational High School - Tang, Nurhidayah; Takdir, Muhammad; Tahir, M. Hijaz; Nurmayanti, Nurmayanti (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study aims to determine the effect of using of Prezi-based Media on Learning Outcomes Indonesian Language Class Student XI at Muhammadiyah Rappang Vocational High School.The study uses a quantitative methodology with a true experimental design with a posttest-only control group design. The population of this study was class XI students totaling 30 people with a sample taken from the entire class XI as many as 30 students of class XI Muhammadiyah Rappang and using saturated sampling technique. There are 2 variables in this study, namely the use of Prezi-based media (independent variable) and Indonesian language learning outcomes of grade XI students (dependent variable). This research was conducted in class XI of Muhammadiyah Rappang Vocational High School. Data collection techniques used observation, documentation, and test techniques. The test data that has been collected is then analyzed using the mean formula and t-test. Based on the results of data analysis, the mean value of the experimental group = 77,333 and the mean value of the control group = 52,444. And in the t-test obtained t-count 4,383> from t-table 5% (2,046) and 1% (2,763) with db 28.Based on the results of this study, it can be concluded that the hypothesis (H1) which states the Effect of Prezi-Based Media Use on Indonesian Language Learning Outcomes of Class XI Studentsof Muhammadiyah Rappang Vocational High School is "accepted".